A corpus-based comparison of Indonesian and English adjectives in Toba Caldera tourism promotional texts - Eva Tuckyta Sari Sujatna; Robert Sibarani; Dadang Sunendar; Defri Elias Simatupang; Alyssa Myrelia Nafhanda; Zahra Elok Asmanida (Studies in English Language and Education, 2026)
Besides being one of the ten UNESCO Global Geoparks (UGGp) in Indonesia, Toba Caldera is also designated as one of the country’s five super-priority tourism destinations. In promoting the Toba Caldera to the global audience, tourism promotional texts play an important role in enhancing cross-linguistic understanding of adjective use and in contributing to knowledge of linguistic and stylistic strategies for effective tourism communication. Word choice, commonly referred to as diction in promotional texts, has a significant impact on readers, especially through the use of adjectives. Adjectives in tourism promotional texts are not limited to descriptions of destinations; they also convey tourists’ emotions and experiences. This research aimed to compare the syntactic and semantic use of adjectives in Toba Caldera tourism promotional texts in both Indonesian and English using a corpus-based approach. To obtain a reliable description of the data, both qualitative and quantitative methods were employed. Due to limited resources, the researchers were able to collect Toba Caldera promotional texts from only 37 Indonesian articles and 80 English articles. The findings reveal that adjectives accounted for 8.2% of the Indonesian corpus and 11.9% of the English corpus. Syntactically, the findings indicated that attributive adjectives occur more frequently than predicative adjectives in both Indonesian and English texts. Semantically, neutral connotative adjectives were found to be dominant in both language versions, surpassing the use of negative and positive adjectives in tourism promotional texts.